Koperasi sebagai Pilar Pengadaan Makanan Bergizi Gratis: Cooperatives as the Pillar of Free Nutritious Food Procurement - Titis Putri Pinasti; Lalu Mariawan Alfarizi (Journal Juridisch, 2025)
This study aims to analyze the actual conditions of consumer cooperatives’ participation in the Free Nutritious Meal (MBG) Program in Semarang City and to identify the inhibiting and supporting factors influencing the optimization of their role within the program. The research is motivated by the limited engagement of cooperatives in the MBG initiative, despite their substantial potential as community-based economic institutions. The urgency of this study lies in the necessity to develop strategies that empower cooperatives as strategic partners in providing nutritious food, particularly in addressing challenges of child nutrition and unequal access to healthy meals. Employing a normative method combined with a qualitative approach based on secondary data and legal framework analysis, the study examines both regulatory and practical dimensions. The findings indicate that among the 15 cooperatives analyzed, only 26.7% had ever participated in school meal provision, and such involvement remained incidental and unsystematic. The novelty of this research underscores the redefinition of cooperatives’ roles—not merely as economic actors but as integral pillars in fostering sustainable school-based food security. The study concludes by emphasizing the need for affirmative policies, improved technical capacity, greater access to flexible financing, and stronger collaboration among government institutions, schools, and cooperatives to establish an inclusive and resilient ecosystem for nutritious food provision.   Penelitian ini bertujuan untuk menganalisis kondisi aktual keterlibatan koperasi konsumen dalam Program Makan Bergizi Gratis (MBG) di Kota Semarang serta mengidentifikasi faktor penghambat dan pendukung dalam optimalisasi peran koperasi pada program tersebut. Latar belakang penelitian ini didasarkan pada masih terbatasnya partisipasi koperasi dalam program MBG, meskipun koperasi memiliki potensi besar sebagai lembaga ekonomi kerakyatan. Urgensi penelitian terletak pada perlunya strategi penguatan koperasi agar mampu berperan sebagai mitra strategis dalam penyediaan makanan bergizi, khususnya di tengah tantangan gizi anak dan ketimpangan akses terhadap pangan sehat. Metode penelitian menggunakan pendekatan yuridis normatif dengan analisis kualitatif berbasis data sekunder dan kajian kerangka hukum untuk menelaah aspek regulatif dan praktik pelaksanaannya. Hasil penelitian menunjukkan bahwa dari 15 koperasi yang dikaji, hanya 26,7% yang pernah terlibat dalam penyediaan makanan bagi sekolah, dan keterlibatan tersebut masih bersifat insidental serta belum terstruktur. Kebaruan penelitian ini menekankan perlunya redefinisi peran koperasi, bukan hanya sebagai entitas ekonomi, tetapi juga sebagai pilar penting dalam pembangunan ketahanan pangan sekolah yang berkelanjutan. Penelitian ini menyimpulkan pentingnya kebijakan afirmatif, peningkatan kapasitas teknis koperasi, perluasan akses pembiayaan yang fleksibel, serta penguatan sinergi antara pemerintah, sekolah, dan koperasi guna membangun ekosistem penyediaan pangan bergizi yang inklusif dan berdaya tahan.